Sky Wolf's call : the gift of indigenous knowledge - Yellowhorn, Eldon, 1956-; Lowinger, Kathy (Annick Press, 2022)
Explores Indigenous knowledge of the natural world through the use of fire and water, the acquisition of food, the study of astronomy, and healing practices. Includes color photographs, a glossary, and additional resources.